Delayed Reimplantation of Avulsed Maxillary Central Incisors: A Case Report (International Journal of Environmental Sciences, 2025)
A 13-year-old boy reported to the dental operatory with a history of trauma. He had a fall from motorcycle and on examination it was noted that due to the impact his 11 and 21 had avulsed out in total. He came to Dental college with both the teeth wrapped in tissue paper. Although the tooth was in highly unfavorable storage condition, with extraoral time being more than 3hrs, it was still decided to re-implant the teeth since the patient was young and to relieve him from psychological, cosmetic and functional trauma. Even though the long-term prognosisis uncertain, this treatment technique has proven to be an advantage for the patient in this growing period by maintaining the esthetics, by maintaining the height of alveolar bone and making the provision of an aesthetically acceptable permanent restoration at a later age if in case prognosis becomes poor.